Efficient production of aromatics by catalytic pyrolysis of fruit waste over zeolites with 3D pore topologies. (15th May 2021) - He, Yao; Chen, Junjie; Li, Didi; Zhang, Qian; Liu, Dongxia; Liu, Jingyong; Ma, Xiaoqian; Wang, Tiejun
Abstract: Fruit waste collected from a juice factory was pyrolyzed over zeolite catalysts with different pore topologies. The production of aromatic compounds was directly influenced by zeolite topology type (i.e. pore opening size and pore channel dimensionality). Zeolites with three-dimensional (3D) pore topologies (e.g. MFI, BEA and FAU) favored aromatization reactions, which yielded up to 80% aromatic compounds, compared to <20% yield in the pyrolysis over FER and MOR zeolites with two- and one-dimensional pore channels, respectively. The catalytic performance of the 3D zeolites, MFI, BEA and FAU were more vulnerable to operating conditions such as catalyst to biomass ratio and pyrolysis temperature, compared to 2D FER and 1D MOR zeolites. The results were possibly explained by the interplays of diffusion limitations and space constrains, imposed by the pore topologies. By correlation analysis, applying FAU zeolite at catalyst to biomass ratio of 2:1 under 450, 550, or 650 °C was found to be optimal for aromatics formation, affording more mono aromatic hydrocarbons (45%) and less polycyclic aromatic hydrocarbons (30%). Moreover, the zeolites employed in the reactions with larger pore size tended to coke. This work potentially provides a guideline for efficient conversion of fruit waste to aromatic compounds enriched biofuels. Graphical abstract: Image 1 Highlights: 3D zeolites favored aromatics formation yielding up to 80%. Catalytic performances of 3D zeolites were more susceptible to pyrolysis conditions. Pore channel dimensionality interplayed with opening size in pyrolysis process. FAU zeolite with high addition was optimal for mono aromatics production.